Civic Activity in Non-Governmental Organizations for Ensuring Security of Local Communities - Kamila Jakubczak-Krawczyńska; Joanna Majchrzyk-Mikuła (Journal of Modern Science)
Objectives The aim of the article is to identify the role that the activity of members of these communities organized in non-governmental organizations plays in ensuring the safety of local communities. The article also aims to identify factors that favor and disfavor the creation of grassroots social initiatives in conditions of deficiencies in civil society, which allow for a more complete understanding of the opportunities and challenges related to the use of social potential to ensure the security of local communities.